2017
DOI: 10.3389/fnbeh.2017.00193
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Testosterone Administration and Digit Ratio (2D:4D) on Implicit Preference for Status Goods in Healthy Males

Abstract: Testosterone has been linked to social status seeking in humans. The present study investigated the effects of testosterone administration on implicit and explicit preferences for status goods in healthy male participants (n = 64), using a double-blind, placebo-controlled, between-subjects design. We also investigated the interactive effect between second-to-fourth digit ratio (2D:4D; i.e., a proximal index of prenatal testosterone) and testosterone treatment on status preferences. Results showed that testoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
2
7
0
1
Order By: Relevance
“…Our findings contribute to other recent pharmacological studies using different behavioural paradigms, and suggest a causal role of testosterone in status-enhancing behaviors that depend on the social context. For instance increase preference for high status goods (Nave et al, 2018;Wu et al, 2017), increase willingness to punish a proposer who proposed an unfair offer in an Ultimatum Game, and increase willingness to reward those who propsed a fair offer (Dreher et al, 2016). Future studies could test if our findings of testosterone in individuals with unstable low social status also extend to behaviors in these paradigms.…”
Section: Discussionmentioning
confidence: 87%
“…Our findings contribute to other recent pharmacological studies using different behavioural paradigms, and suggest a causal role of testosterone in status-enhancing behaviors that depend on the social context. For instance increase preference for high status goods (Nave et al, 2018;Wu et al, 2017), increase willingness to punish a proposer who proposed an unfair offer in an Ultimatum Game, and increase willingness to reward those who propsed a fair offer (Dreher et al, 2016). Future studies could test if our findings of testosterone in individuals with unstable low social status also extend to behaviors in these paradigms.…”
Section: Discussionmentioning
confidence: 87%
“…2D:4D is also thought to be a marker of the short‐term activational effects of adult testosterone. Men with lower 2D:4Ds tend to experience more marked spikes in testosterone during challenging situations (eg, in competitive sports) (Kilduff, Hopp, Cook, Crewther & Manning, ; Kilduff et al, ), and 2D:4D modulates the effects of exogenous testosterone application on empathy, moral judgments, cooperation, aggression, status, and para‐hippocampal activity associated with mental rotation task scores in men (Carré et al, ; Wu, Zilioli, Eisenneger, Clark & Li, ) and women (van Honk, Montoya, Bos, van Vugt & Terburg, ; van Honk, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies have found that digit ratios in men were not significantly associated with dominance (Putz, Gaulin, Sporter, & McBurney, 2004;Vermeersch, T'Sjoen, Kaufman, & Vincke, 2008), competitiveness (Apicella et al, 2011), risk taking (Apicella et al, 2008;Aycinena, Baltaduonis, & Rentschler, 2014;Sapienza et al, 2009), and preferences for status goods (Nave et al, 2018). Similarly, research has found that circulating testosterone levels in men were not significantly associated with aggression (Archer, Birring, & Wu, 1998), competitiveness (Apicella et al, 2011), financial risk taking (Sapienza et al, 2009), and conspicuous consumption (Wu et al, 2017). Thus, although there are studies suggesting that prenatal testosterone exposure and circulating testosterone are associated with status-related dispositions and decision making, when we take these null findings into account, the overall literature is mixed.…”
Section: Moderating Role Of Personality Traits and Situational Variablesmentioning
confidence: 99%
“…Notably, numerous studies examining the effects of prenatal (Nave et al, 2018) and circulating testosterone (Wu, Zilioli, Eisenegger, Clark, & Li, 2017) on status-related decision making have found null results. Interestingly, some research indicates that the effects of prenatal testosterone exposure (Cornelissen & Palacios-Fenech, 2016;Millet & Dewitte, 2008;Nepomuceno, Saad, Stenstrom, Mendenhall, & Iglesias, 2016a;Otterbring et al, 2018;Ryckmans, Millet, & Warlop, 2015) and circulating testosterone (Carré & Archer, 2018;Slatcher, Mehta, & Josephs, 2011) on statusrelated decision making only emerge when considering certain personality traits or situation.…”
mentioning
confidence: 99%